Comparação dos indicadores financeiros das empresas de pet shops entre mercados brasileiros e americanos - Ribeiro, Cristiano dos Anjos (2023)
The carried out consists of mapping, researching and comparing the main financial indices of three companies in the pet shops market. One of them is Brazilian Petz and two others from the American market, Pet Co. were obtained, with the data obtained from the balance sheets of the companies, during the period from 2020 to 2022, with the objective of identifying and the period when the main and largest Brazilian company in the pet shops sector is on the same financial level as the American ones. In general, considering that the market still informs, it was observed that it needs more and more professionals prepared to analyze a data market. Managers, decision leaders and professionals, decision makers, increasingly with intelligent intelligence, assisting as entities in strategic vision and decision making